Studi Perencanaan Usaha Keripik Kaca Menggunakan Business Model Canvas - Maulida, Ayuni Rizma; Haryanto, Andre Geza (Journal of Food and Culinary, 2020)
The business world needs a business plan that can help entrepreneurs prepare everything needed for the smooth running of their business. This business plan can be made in the form of a business plan. One business plan model that has many advantages is the Business Model Canvas. The purpose of writing this article is to find out what needs to be considered in making a business plan using the Business Model Canvas. The results of the literature review show that using the Business Model Canvas business planning becomes clearer and more focused. The glass chip business, which is an example in the application of the canvas business model, is becoming more focused and clear. Therefore, in making a business model, the canvas has 9 important components, including Customer Segment, Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Activities, Key Partnerships, Key Resources and Cost Structures that need to be considered and structured clearly to help run the business.Keywords: business, Business Model Canvas, business plan, glass chips, planningABSTRAKÂ Dunia usaha memerlukan suatu perencanaan usaha yang dapat membantu wirausahawan menyiapkan segala sesuatu yang dibutuhkan untuk kelancaran usahanya. Perencanaan usaha ini dapat dibuat dalam bentuk business plan. Salah satu model business plan yang banyak memiliki keuntungan yaitu Business Model Canvas. Tujuan dari penulisan artikel ini adalah untuk mengetahui apa saja yang perlu diperhatikan untuk membuat perencanaan usaha menggunakan Business Model Canvas. Hasil dari penelaahan pustaka menunjukkan dengan menggunakan Business Model Canvas perencanaan usaha menjadi lebih jelas dan terarah. Usaha keripik kaca yang menjadi contoh dalam penerapan Business Model Canvas ini menjadi lebih terarah dan jelas. Oleh karena itu dalam pembuatan Business Model Canvas memiliki 9 komponen penting diantaranya Customer Segment, Value Propositions, Channel, Customer Relationship, Revenue Streams, Key Activities, Key Partnership, Key Resources dan Cost Structure yang perlu diperhatikan dan disusun dengan jelas agar membantu kelancaran usaha.Â Kata Kunci: Business Model Canvas, business plan, keripik kaca, perencanaan, usaha